2022
DOI: 10.3389/fimmu.2022.1030238
|View full text |Cite
|
Sign up to set email alerts
|

Post-vaccination SARS-CoV-2 seroprevalence in children aged 3-11 years and the positivity in unvaccinated children: A retrospective, single-center study

Abstract: ObjectiveTo analyze the positivity and levels of SARS-CoV-2 antibodies in vaccinated children to evaluate the humoral immune response of vaccination on pediatric population. Analysis on the causes of antibody positivity in unvaccinated children.MethodsA retrospective study was conducted on children who were admitted to the Children’s Hospital Affiliated to Capital Institute of Pediatrics. The clinical data of serological testing of SARS-CoV-2 immunoglobulin M (IgM) and IgG antibodies were collected from SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the present investigation, approximately half of the preschool-aged children had received two doses of the SARS-CoV-2 vaccine, with the majority receiving the second dose at least six months prior to infection. As vaccination time passed by, the humoral immune response-induced antibody production declined to levels similar to baseline at the time of infection ( 29 , 30 ). The current study revealed no discernible association between vaccination status and the incidence of persistent symptoms in children.…”
Section: Discussionmentioning
confidence: 98%
“…In the present investigation, approximately half of the preschool-aged children had received two doses of the SARS-CoV-2 vaccine, with the majority receiving the second dose at least six months prior to infection. As vaccination time passed by, the humoral immune response-induced antibody production declined to levels similar to baseline at the time of infection ( 29 , 30 ). The current study revealed no discernible association between vaccination status and the incidence of persistent symptoms in children.…”
Section: Discussionmentioning
confidence: 98%
“…Our analysis for VE against the Omicron BA.5 infection showed that among children and adolescents, the risk of infection by the BA.5 variants for individuals who received a two-dose inactivated vaccine reduced by 92.4% within six months (75.4% for those who have received a two-dose inactivated vaccine for 181–365 days) (Supplementary Data 1 ), as compared to those who only received a one-dose inactivated vaccine and those who received the two-dose regimen for more than a year. Considering a one-dose vaccine only provided a weak immune response and protection against SARS-CoV-2 infection, and the immunity level would wane to a considerably lower level a year after receiving the second dose of the inactivated vaccine 19 , 32 , 33 , 50 , our reference group might represent the group of children and adolescents who have a relatively lower internal immunity induced by the vaccine. Furthermore, the estimated risk reduction not only reflected the additional protection conferred by a second dose of vaccine compared to a one-dose vaccine but also a waned VE.…”
Section: Discussionmentioning
confidence: 99%
“…We thus removed unvaccinated children from analyses and restricted our attention to the VE of two-dose against one-dose vaccines. In view of the small sample size for close contacts who received only one-dose vaccine, we considered individuals who received two-dose vaccine over 365 days as a complement of the reference group, assuming the vaccine-elicited immunity remained after 1 year was at a relatively low level 32 , 33 .…”
Section: Methodsmentioning
confidence: 99%
“…However, those children with a few months old than 6 years in the sample collection period (February 10 to March 10, 2023) were less likely vaccinated, since China school year starts September 1 of each year and they were less than 6 years old in September of 2022. Moreover, the significantly higher (around 10-fold) titers of anti-N/S1 IgG (Figure 2) suggest a booster caused by natural infection, because vaccination with inactivated COVID-19 vaccines usually induces relatively low antibody titers and wanes rapidly within several months (12).…”
Section: Discussionmentioning
confidence: 99%